Quest for Identity: A Study of Henrik Ibsen’s The Lady from the Sea: Exploring the struggle for identity in Henrik Ibsen's The Lady from the Sea (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Identity is said to be a social phenomenon which is created by society and it plays a very crucial role in the life of every individual. The theme of identity has been taken in the present research paper and the playwright tries to explore the struggle of the central character concerning the quest for identity in the male dominated society of Norwey. The quest for identity has been an seminal theme for all the major writers of the nineteenth century. Henrik Ibsen is one of those writers who deal with the problems of women regarding their identity. His play, The Lady from the Sea, is written in a symbolic mode and it explains how women can realise their identity when they overcome the biased and illogical hurdles created by men in the society to subordinate women. Having made full use of symbolism, Henrik Ibsen emphasises on the quest for identity, specifically through the protagonist of the play and a kind of transformation in all the characters can be observed in the end of the play.